# How do you solve #0.5( x + 2.8) - x = 0.6x + 0.3#?

By signing up, you agree to our Terms of Service and Privacy Policy

To solve the equation 0.5(x + 2.8) - x = 0.6x + 0.3, follow these steps:

- Distribute 0.5 into the parentheses: 0.5x + 1.4 - x = 0.6x + 0.3
- Combine like terms on both sides of the equation: 0.5x - x + 1.4 = 0.6x + 0.3
- Simplify the left side: -0.5x + 1.4 = 0.6x + 0.3
- Move all terms involving x to one side and constants to the other side: -0.5x - 0.6x = 0.3 - 1.4
- Combine like terms: -1.1x = -1.1
- Divide both sides by -1.1: x = 1

By signing up, you agree to our Terms of Service and Privacy Policy

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7